A cross sectional study reflecting association between common menstrual disorders and college absenteeism - Shete, Jagannath S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Menstrual disorders affect half of all female adolescents and represent leading cause of periodic college absenteeism but awareness regarding health seeking behaviour is less. Objective was to study association between common menstrual disorders and college absenteeism in first and second year medical students in Mumbai. Methods: 150 female students from first and second year MBBS were included in the study. Research tool comprised of questions about demographic characteristics, age at menarche, menstrual cycle pattern, complaints and its impact on daily activities including college absenteeism. Behaviour towards health and knowledge about menstrual cycle was observed. Percentage and chi square values were calculated using SPSS 16. The study was conducted in period between August to October 2012. Results: 150 first and second year female medical students participated in the study. Their mean age was 19.5 yrs. Mean age of menarche was 13-14 years in 78%. Menstrual cycle was regular in 72.6%. Menstrual flow was average in 73.3% of respondents and 88% reported duration as 3-5 days. 92% respondents had painful menses especially reporting moderate pain in 78% while in 70% of those pain resolved on its own. 67.4% reported mother as source of menstrual cycle information. Although menstrual disorder was cause of college absenteeism of 1-2 days in 44% students, 88% students didn’t seek medical advice for menstrual disorders. Conclusions: Improving health seeking behaviour towards common menstrual problems can reduce college absenteeism.